A step change towards sustainable aviation fuel from sewage sludge - Bashir, Muhammad Asif; Lima, Sergio; Jahangiri, Hessam; Majewski, Artur J.; Hofmann, Martin; Hornung, Andreas; Ouadi, Miloud (Journal of Analytical and Applied Pyrolysis, 2022)
Sewage sludge, an abundant and problematic organic waste, was successfully converted into sustainable jet fuel range hydrocarbons (C8-C16). Sewage sludge was pre-conditioned and processed through a Thermo-Catalytic Reforming (TCR) system (2 Kg/h) at 450 ºC pyrolysis and 700 ºC post-reforming temperature to produce a biocrude oil. The bio-crude oil was subsequently conditioned and upgraded via consecutive two-step hydroprocessing, comprising hydrodeoxygenation and hydrocracking as two separate unit operations. The two-step hydroprocessing was carried out in a bench-scale batch high-pressure reactor (autoclave). The process parameters such as temperature, feed volume, catalyst loading, and batch time were held constant, whilst the H2 pressure was varied. The effect of H2 pressure across 30 – 60 bar on the quality of the hydroprocessed oil was evaluated in terms of elemental composition, chemical compound distribution, and fuel properties. Hydroprocessing at 60 bar H2 resulted in better fuel properties compared to hydroprocessing at 30 bar H2. Hence, approximately 25% by weight jet fuel fraction, including normal, cyclo and iso-paraffins and aromatics in the C8–C16 range, was recovered via atmospheric distillation of the hydroprocessed oil at 60 bar H2. Sewage sludge derived jet fuel range fraction met the majority of the jet fuel specifications for calorific value, viscosity, density, and freeze point under the ASTM D7566 standard. Some parameters such as smoke, flash point and total acid number slightly fell out of specifications. The process also produced green naphtha and diesel as by-products. In addition, the process was further tested for catalyst reusability and regeneration potential that showed promising results for future research.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Biofuels; Hydrocracking; Hydrodeoxygenation; Jet Fuel; TCR; Waste